Potential Use of High Pressure Homogenized Hazelnut Beverage for a Functional Yoghurt-Like Product - OSMAN GUL; ILYAS ATALAR; MUSTAFA MORTAS; FURKAN TURKER SARICAOGLU; AYSEGUL BESIR; LATIFE BETUL GUL; FEHMI YAZICI (Anais da Academia Brasileira de Ciências, 2022)
Abstract Hazelnut beverage is a plant-based beverage produced from hazelnut cake as a by-product obtained after cold press extraction. It has high nutritional value and a significant percentage of consumers show interest in it due to its health benefits. In this study, hazelnut beverage manufactured from by-products of hazelnut oil industry was incorporated into functional yoghurt production. Five formulations (ratio of 1/0, 3/1, 2/1, 1/1, 0/1, v/v, cow milk/hazelnut beverage) of yoghurt-like products were prepared to indicate the storage period of the samples and the analysis performed. For yoghurt production, hazelnut beverage and cows’ milk were standardized to 14.5 g 100 g-1 with skimmed milk powder. The use of hazelnut beverage in yoghurt production negatively affected L. bulgaricus counts. Water holding capacity and viscosity values were improved by using hazelnut beverage. Increasing hazelnut beverage concentration led to an increase in the total phenolic compounds and antioxidant activity, malic acid levels and also unsaturated fatty acids, especially oleic and linoleic acid. Using the ratio of 3/1 was found the best in view of appearance, flavor and overall acceptability. Based on the structural, rheological and sensorial properties, this study could guide the dairy industry to use hazelnut beverage obtained from hazelnut cake.